$ y= (x^2+2x+3)^{(1+x^2)} + x^x $
วิธีทำ
\begin{align} & \cssId{Step1}{ ให้ \quad u =(x^2+2x+3)^{(1+x^2)} \quad และ \quad v = x^x \quad จะได้ว่า \quad\frac{dy}{dx} = \frac{du}{dx} + \frac{dv}{dx} } \\ &\cssId{Step2}{จาก \quad u =(x^2+2x+3)^{(1+x^2)} \quad take \quad \ln \quad จะได้ \quad \ln u = (1+x^2) \ln (x^2+2x+3 ) } \\ &\cssId{Step3}{ดังนั้น \quad \frac{1}{u} \frac{du}{dx} = (1+x^2) \frac{d}{dx} \ln (x^2+2x+3 ) + \ln (x^2+2x+3 ) \frac{d}{dx} (1+x^2) } \\ &\cssId{Step4}{ = (1+x^2) \frac{1}{x^2+2x+3} (2x+2 ) + \ln (x^2+2x+3) (2x) } \\ &\cssId{Step5}{ ดังนั้น \quad \frac{du}{dx} = u ( \frac{(1+x^2) (2x+2 )}{x^2+2x+3} + 2x \ln (x^2+2x+3) ) } \\ &\cssId{Step6}{ = (x^2+2x+3)^{(1+x^2)} ( \frac{(1+x^2)(2x+2 )}{x^2+2x+3} + \ln (x^2+2x+3) (2x)) } \\ &\cssId{Step7}{จาก \quad v = x^x take \quad \ln \quad จะได้ \quad \ln v = x \ln x } \\ &\cssId{Step8}{ จะได้ \quad \frac{1}{v} \frac{dv}{dx} = x \frac{1}{x} +\ln x =1+ \ln x } \\ &\cssId{Step9}{ ดังนั้น \quad \frac{dv}{dx} = v(1+\ln x) = x^x (1+ \ln x ) } \\ &\cssId{Step10}{ ดังนั้น \quad \frac{dy}{dx} = (x^2+2x+3)^{(1+x^2)} ( \frac{(1+x^2)(2x+2 )}{x^2+2x+3} + \ln (x^2+2x+3) (2x)) + x^x (1+ \ln x ) } \\ \end{align}